WEB-BASED BASIC ENGLISH GRAMMAR MATERIALS: A NEED ANALYSIS FOR THE FIRST YEAR STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR (International Conference on Social and Islamic Studies, 2021)
Technology is increasingly becoming a trend with a million benefits offered to its users. In a pandemic situation nowadays, the role of technology in the education sector is very important. Thus, this study aims to develop Web-based Basic English Grammar materials. the starting point in developing Web-based Basic English grammar materials is identifying student needs related to Web-based Basic English Grammar Materials. This Research utilized survey research. The subject of this research is the first-year students of English Education Department class A, B and C, which is consist of 100 people. The instrument of the research was questionnaire and interview. The result of the research shows that in terms of display of the the website, students perceive that the website should consists of definition, kinds, examples, and learning videos of basic English grammar materials. Additionally, individual and group assignments are needed to measure students' comprehention of the material.